(untitled) (Journal of Economic Research & Business Administration, 2015)
This article contains the results of studies of formal models of motivation and stimulation procedures in project management. The role of incentives as a means to control the insurance companies persogalom. Considered: incentive mechanisms director of the branch, the front – the branch office, back – office branch, motivation back – office head quarters. Examines the role of information, background information on the divested necessary for effective decisionmaking to promote a project management system. We investigate the properties of modern corporate information systems project management, conclusions about the possibilities of their practical combination with the results of analysis and incentive mechanisms.